2010
DOI: 10.1124/jpet.110.166116
|View full text |Cite
|
Sign up to set email alerts
|

Lubiprostone Reverses the Inhibitory Action of Morphine on Intestinal Secretion in Guinea Pig and Mouse

Abstract: Lubiprostone activates ClC-2 chloride channels in epithelia. It is approved for treatment of chronic idiopathic constipation in adults and constipation-predominate irritable bowel syndrome in women. We tested a hypothesis that lubiprostone can reverse the constipating action of morphine and investigated the mechanism of action. Short-circuit current (Isc) was recorded in Ussing chambers as a marker for chloride secretion during pharmacological interactions between morphine and lubiprostone. Measurements of fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 30 publications
2
40
1
Order By: Relevance
“…The associated delay in colonic transit increases the duration for water absorption. Opioid-dependent hyperpolarization of submucosal neurons leads to reduced secretomotor activity, fur-ther contributing to constipation (13). However, despite the clear physiological role, established value as a therapeutic target and role in mediating the adverse side effects of opiate analgesics on the bowel, surprisingly little is known about the distribution of opioid receptors in the enteric nervous system.…”
Section: This Article Provides a Detailed Characterization Of The -Opmentioning
confidence: 99%
“…The associated delay in colonic transit increases the duration for water absorption. Opioid-dependent hyperpolarization of submucosal neurons leads to reduced secretomotor activity, fur-ther contributing to constipation (13). However, despite the clear physiological role, established value as a therapeutic target and role in mediating the adverse side effects of opiate analgesics on the bowel, surprisingly little is known about the distribution of opioid receptors in the enteric nervous system.…”
Section: This Article Provides a Detailed Characterization Of The -Opmentioning
confidence: 99%
“…[17][18][19] DA-9701 has shown affinity for the dopamine (D) 2 , 5-hydroxytryptamine (5-HT) 4 , 5-HT 1A , and 5-HT 1B receptors. 13,11,15 It has antagonistic effects on the D 2 receptors and agonistic effects on the 5-HT 4 , 5-HT 1A and 5-HT 1B receptors. 14,15,20 It has been reported that DA-9701 can improve delayed gastric emptying and may be effective as a prokinetic agent.…”
mentioning
confidence: 99%
“…Drugs we have worked on in this category include cisapride (Propulsid Ò ), tegaserod (Zelnorm Ò ), alosetron (Lotronex Ò ), and lubiprostone (Amitiza Ò ) [46][47][48].…”
Section: Pharmaceutical Industrymentioning
confidence: 99%